Ownership concentration, institutional development and firm performance in Central and Eastern Europe - Benjamin Balsmeier; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper analyzes the relationship of ownership concentration and firm performance in the context of different institutional environments in 28 Central and Eastern European transition economies. Using the BEEPS data for the period from 2002 to 2009 we find an inverted u-shaped relation of ownership concentration and firm performance for those firms that operate in non-EU-member countries as well as those firms that are situated in less developed legal systems according to Freedom House ratings. We interpret these findings as evidence for a classic agency problem in the lower part of the ownership concentration distribution that is dominated by a 'private benefits of control' problem with rising ownership concentration.
Keywords: G32; L25; O16; P31; 330; corporate governance; firm growth; transition economies; ownership concentration; Corporate Governance; Eigentümerstruktur; Unternehmensentwicklung; Übergangswirtschaft; Institutionelle Infrastruktur; Rechtsstaat; Vergleich; Osteuropa; EU-Staaten (Osteuropa)